Analysis and design of eccentrically compressed ultra-high-strength slender CFST circular columns. (October 2020) - Phan, Dao Hoang Hiep; Patel, Vipulkumar Ishvarbhai; Al Abadi, Haider; Thai, Huu-Tai
Abstract: There has been an increasing interest in the application of ultra-high-strength concrete considering the high strength and stiffness compared to conventional concrete. The current international design standards do not allow for the use of ultra-high-strength concrete in composite members. This is due to the limited studies on ultra-high-strength CFST circular columns. In line with this, the objective of the current paper is to obtain an inelastic behaviour of ultra-high-strength slender CFST circular columns when subjected to eccentric compression loads. No previous numerical study has investigated the axial load-moment performance of ultra-high-strength slender CFST circular columns loaded eccentrically. The fiber element numerical method is employed in the inelastic analysis of ultra-high-strength slender CFST beam-columns. The stress–strain response of concrete considering the effect of the confinement mechanism is adopted in the numerical analysis. The model accuracy was ascertained by the experiment results published in the literature. The experimental result revealed that slender columns under eccentric loading failed by the overall buckling with large lateral deflections. A comprehensive parametric study based on a wide spectrum of column geometry and material properties was conducted. The use of ultra-high-strength concrete is not significant when the beam-column subjected to compression load with the large eccentricity. The European standard underestimates the calculation of ultimate axial strength while the American and Australian standards overestimate the ultimate axial strength of ultra-high-strength slender CFST circular beam-columns under eccentric loading.